The Association Between Mindfulness and Athletes’ Distress Tolerance: The Mediating Roles of Cognitive Reappraisal and Mental Toughness - Zhangyi Zhong; Hongyu Jiang; Huilin Wang; Yang Liu (Behavioral Sciences)
Physical and psychological distress frequently challenges athletes throughout their careers. The perception of pain and coping strategies are often crucial factors in achieving victory. These factors not only reflect their commitment to daily training, but can also indicate their level of athletic performance. This study is a cross-sectional research using convenience and snowball sampling methods. It explores the relationship between mindfulness and athletes’ distress tolerance, revealing the mediating roles of cognitive reappraisal and mental toughness. A sample of 285 athletes was drawn from universities, youth training centers, and sports academies in Hunan, Hubei, and Sichuan provinces in China. To assess the proposed hypotheses, structural equation modeling was conducted using AMOS v23. The findings identified a significant positive correlation between mindfulness, cognitive reappraisal, and mental toughness. Additionally, both cognitive reappraisal and mental toughness were positively associated with distress tolerance. Further analysis demonstrated that cognitive reappraisal and mental toughness function as mediators in the mindfulness–distress tolerance relationship. These results indicate that athletes with higher mindfulness levels exhibit enhanced cognitive reappraisal skills, greater mental toughness, and improved distress tolerance. This means that athletes with higher mindfulness levels are more likely to detach from negative psychological states in a timely manner, utilizing emotional regulation skills such as cognitive reappraisal, and face training and competition with greater mental resilience. This can help athletes alleviate negative psychological states and, to some extent, reduce their experience of pain, enabling them to better cope with challenges. Therefore, athletes can actively engage in mindfulness practices combined with cognitive reappraisal strategies to achieve better psychological states, which can support their adherence to training and rehabilitation plans.